PENGARUH DISIPLIN TERHADAP EFEKTIVITAS KERJA PEGAWAI DI KELURAHAN SIDODADI KECAMATAN SAMARINDA ULU KOTA SAMARINDA - Rusli Rusli; Vigya Asriani (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2022)
Work discipline in the context of public organization management plays a major role in creating qualified human resources and qualified human resources will be seen from the effectiveness of their performance. This article wants to discuss the effect of discipline on the work effectiveness of employees in Sidodadi Village. By using a quantitative approach with total sampling technique and Rank Spearman correlation analysis it was found that work discipline has an influence on the work effectiveness of Sidodadi Village employees.